2009
DOI: 10.1007/s00066-009-1892-0
|View full text |Cite
|
Sign up to set email alerts
|

Ist die Kardiotoxizität der Radiotherapie im Rahmen des Brusterhalts überhaupt noch relevant, und könnte sie durch Mehrfelder-IMRT gesenkt werden?

Abstract: This review updates the database on cardiac toxicity of breast cancer radiotherapy with special emphasis regarding the issues related to the clinical use of IMRT. Multifield IMRT may reduce the cardiac risk for a small subset of patients at excessive risk with conventional tangential radiotherapy due to unfavorable thoracic geometry, for whom partial-breast radiotherapy is not an option. Due to further concern about the effects of intermediate doses to larger heart volumes, potentially increased contralateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 90 publications
1
6
0
Order By: Relevance
“…Similar data were reported for patients undergoing radiotherapy for lung cancer [7]. Nowadays, special attention is also paid to females treated with adjuvant radiotherapy for left-sided breast cancer as it has been shown that these patients also have an increased risk of chronic cardiac morbidity [17] due to a significant radiation exposure to the heart [4]. While the threshold dose for irradiation-induced cardiac morbidity remains controversial, tolerance doses recommended today are 40 Gy and are thus similar to other radiosensitive organs [25].…”
Section: Introductionsupporting
confidence: 65%
“…Similar data were reported for patients undergoing radiotherapy for lung cancer [7]. Nowadays, special attention is also paid to females treated with adjuvant radiotherapy for left-sided breast cancer as it has been shown that these patients also have an increased risk of chronic cardiac morbidity [17] due to a significant radiation exposure to the heart [4]. While the threshold dose for irradiation-induced cardiac morbidity remains controversial, tolerance doses recommended today are 40 Gy and are thus similar to other radiosensitive organs [25].…”
Section: Introductionsupporting
confidence: 65%
“…Since HT is almost always used in combination with RT, it would be beneficial to integrate the RT CT scan in both planning techniques [1,12,17,18,19,27,32]. However, this is not possible for SHT and deep HT treatments, since the positioning for RT differs from that for HT.…”
Section: Discussionmentioning
confidence: 99%
“…However, in an experimental dosimetric study, dose inhomogeneities with an underdosage by approximately 10% in parts of the planning target volume are described [37]. In cases with relevant dose inhomogeneities intensity-modulated radiation treatment or segmented techniques allow to optimize the dose distribution [1,14,18,19]. Generally, treatment plans should be performed with a computed tomography-based density correction method to compensate potential artifacts from the metallic port [37].…”
Section: Discussionmentioning
confidence: 99%